Un « cas exécrable » devant le Parlement de Paris à la fin des guerres de Religion (1599-1600) - Tom Hamilton (Criminocorpus)
This case, tried by the magistrates of the Parlement of Paris in 1599 and 1600, sheds new light on the local dynamics of violence in the later religious wars as well as the judicial responses pursued by its victims. The case came to court on the initiative of the plaitiff, Renée Chevalier, dame de Chaumot, who assembled dozens of witnesses to testify to the many rapes, thefts, and homicides committed by the military captain Mathurin Delacanche in their village in the Sénonais during the winter of 1590-1. The dispute serves as a case study in the application of eighty-six of the Edict of Nantes, concerning the « execrable crimes » which were exempt from the famous order in the edict’s first article, which consigned the troubles to oblivion. Presented here for the first time, the surviving documents in this affair constitute one of the most detailed cases preserved in the criminal archives of the Parlement of Paris in the sixteenth century.